Electroacupuncture Reduces Postoperative Pain and Analgesic Consumption in Patients Undergoing Thoracic Surgery: A Randomized Study - Chen, Tongyu (Evid Based Complement Alternat Med, 2016)
The aim of this study was to evaluate the effect of electroacupuncture (EA) on postoperative pain management in patients undergoing thoracic surgery. A randomized study was conducted. Ninety-two thoracic surgical patients were randomly divided into an EA group and a sham group. Postoperative intravenous analgesia was applied with a half dose of the conventional drug concentration in both groups. In the EA group, EA treatment was administered for three consecutive days after the surgery with 6 sessions of 30 min each. Compared with the sham group, patients in the EA group had a lower visual analogue scale (VAS) score at 2, 24, 48, and 72 hours and consumed less analgesic after surgery. The incidence of opioid-related adverse effects of nausea was lower in the EA group. The time to first flatus and defecation was also shorter in the EA group. Furthermore, the plasma β-endorphin (β-EP) level was higher by radioimmunoassay and the plasma 5-hydroxytryptamine (5-HT) level was lower in the EA group by enzyme-linked immunosorbent assay during the first 72 hr after thoracic surgery. Therefore, EA is suitable as an adjunct treatment for postoperative pain management after thoracic surgery.